2017
DOI: 10.1016/s0140-6736(17)30341-0
|View full text |Cite
|
Sign up to set email alerts
|

Progress and challenges to introduce midwifery education in Nepal

Abstract: Kisika F. Where do the rural poor deliver when high coverage of health facility delivery is achieved? Findings from a community and hospital survey in Tanzania. PLoS One 2014; 9: e113995. 5Fogliati P, Straneo M, Brogi C, et al. How can childbirth care for the rural poor be improved? A contribution from spatial modelling in rural Tanzania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The test showed that none of the loss in performance score was statistically significant b For skilled birth attendants only mentors further trained and mentored by provincial mentors, as successfully implemented in Uganda in the area of MNC [26]. Nepal has, however, taken a very promising step forward by launching a midwifery education program [27][28][29]. It is expected that the soon-to be deployed midwives will help improve the clinical skills of ANMs and nurses.…”
Section: Sustainabilitymentioning
confidence: 99%
“…The test showed that none of the loss in performance score was statistically significant b For skilled birth attendants only mentors further trained and mentored by provincial mentors, as successfully implemented in Uganda in the area of MNC [26]. Nepal has, however, taken a very promising step forward by launching a midwifery education program [27][28][29]. It is expected that the soon-to be deployed midwives will help improve the clinical skills of ANMs and nurses.…”
Section: Sustainabilitymentioning
confidence: 99%
“…Indeed, Nepal transcended lackluster performance globally to become one of the first countries to meet its maternal mortality targets in 2013, rapidly being celebrated as a redemptive success story [11]. The government has proven a consistent partner in this progress, having enacted a National Policy on Skilled Birth Attendants that has overseen the training of 7,000 SBAs since 2006 [12–16]. A more critical subnational analysis reveals persistent inequalities: Maternal deaths remain disproportionately high in the mountainous district, compared with the hills and lowland Terai, as well as among lower socioeconomic classes.…”
Section: Introductionmentioning
confidence: 99%
“…By deploying midwives who are educated to ICM standards, especially low-income countries as highlighted in The Lancet series on midwifery [22][23][24] many maternal deaths and neonatal stillbirths can be avoided 25 . However, a specific midwifery curriculum is currently under review 26 . Hence general nurses, with less than one year of maternity training are the key maternity and mental health care providers in Nepal.…”
Section: Nursing Education and Training In Nepalmentioning
confidence: 99%